IgE auto-antibodies to human fatty acid-binding proteins in atopic dermatitis patients (2020)
ABSTRACT: IgE auto-antibodies have been described in some allergic diseases, especially in atopic dermatitis (AD). Clinical implications of these antibodies in allergies are not fully understood, but IgE sensitization to self-proteins may represent an important mechanism involved in the maintenance of severe chronic forms. The aim of this study was to explore the presence of the auto reactive IgE response to endogenous fatty acid-binding proteins (FABPs) from the heart (FABP3) and adipocytes (FABP4), two proteins homologous to group 13 of house dust mite (HDM) allergens, in patients with AD. Seventy-one patients with AD and sixty individuals without AD were recruited. After complete clinical evaluation and informed consent, skin prick test (SPT) and serum IgE, IgG and IgG4 levels were determined using extracts of Dermatophagoides pteronyssinus and Blomia tropicalis, the recombinants FABP3 and FABP4, and the allergen Blo t 13. The frequency of positive IgE levels to FABP3 and FABP4 in AD group was 61 and 52%, respectively. Patients with positive IgE auto-reactivity to human FABPs were also sensitized to Blo t 13. IgG and IgG4 levels to FABP3 and FABP4 were detected in all AD patients and no-AD subjects, with the antibody levels in no-AD subjects being significantly higher than those in AD patients. In conclusion, patients with AD, who had positive SPT and serum IgE levels to Blo t 13 allergen showed serum IgE and IgG antibodies against FABP3 and FABP4. The molecular mimicry with HDM allergens could explain this finding, which could contribute to the pathomechanism of AD.